WOMEN'S VOICES IN THE LUCIANIC ONOS: THE TALE OF THE 'EDIBLE MAN'. (December 2015) - Dollins, Elizabeth
Abstract : This article argues that female characters are active participants in the text of the Onos . Among women who are in control of their experiences we encounter the slave girl Palaestra. She uses a forceful metaphor equating a man with the food being prepared in her kitchen, which prefigures much of the ensuing narrative and has the effect of transforming Lucius into food/text to be consumed by the reader. It becomes clear that she and various other female characters, whose abilities go further than the usual novelistic antagonistic skill of controlling their own experience and manipulating other characters, choose and choreograph Lucius' narrative.